(untitled) (Medical Forum Monthly, 2021)
Objective: To find the students’ preference between zoom online and traditional face to face Physiology teaching in undergraduate physical therapy and biotechnology & biological sciences during the COVID-19 pandemic. Study Design: Cross Sectional study Place and Duration of Study: This study was conducted at the Sohail University from April 2021 to June 2021 for a period of 02 months. Materials and Methods: The study participants included 100 Physical therapies and 94 Biotechnology & Biological sciences students. A questionnaire was distributed to each student. The questionnaire included 17 items regarding online and traditional teaching. The students were asked to select a response for each item on the questionnaire including the preferred teaching method from zoom online, traditional, or both. The data were presented in terms of percentage for the individual items, preference in theory, and the overall preferred teaching method. Results: The students gave the opinion that the presence of teacher (82.1%), asking the queries to the teacher (80.2%), giving feedback to the teacher (78.3%), and interest in learning (76.4%) were more important aspects for traditional teaching. Regarding the zoom online lectures, accessibility to the internet hindered online teaching (84%) and online teaching led to more distraction (67.9%). Moreover, a high majority of students (79.2%) preferred the traditional method for theory. The overall preference for the traditional method (83%) was higher as compared to online (2.8%) and both methods (14.2%). Conclusion: The majority of physical therapy and Biotechnology & Biological sciences students had a preference for traditional teaching methods in Physiology.